2009
DOI: 10.1063/1.3276555
|View full text |Cite
|
Sign up to set email alerts
|

DNA-psoralen: Single-molecule experiments and first principles calculations

Abstract: The authors measure the persistence and contour lengths of DNA-psoralen complexes, as a function of psoralen concentration, for intercalated and crosslinked complexes. In both cases, the persistence length monotonically increases until a certain critical concentration is reached, above which it abruptly decreases and remains approximately constant. The contour length of the complexes exhibits no such discontinuous behavior. By fitting the relative increase of the contour length to the neighbor exclusion model,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 20 publications
(24 reference statements)
9
28
0
Order By: Relevance
“…Such behavior of the persistence length appears to be a general property of DNA‐intercalator complexes when stretched under the force regime of F< 5 pN . In fact, the same qualitative behavior was previously verified under our experimental conditions for the intercalators ethidium bromide, daunomycin, psoralen, diaminobenzidine and for the bis‐intercalator gelred . As detailed discussed in Ref.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Such behavior of the persistence length appears to be a general property of DNA‐intercalator complexes when stretched under the force regime of F< 5 pN . In fact, the same qualitative behavior was previously verified under our experimental conditions for the intercalators ethidium bromide, daunomycin, psoralen, diaminobenzidine and for the bis‐intercalator gelred . As detailed discussed in Ref.…”
Section: Resultssupporting
confidence: 88%
“…In addition, observe that the data obtained in the Tris‐HCl buffer presents the typical shape observed for most intercalators . The data obtained in the PBS buffer, on the other hand, exhibits a slightly sigmoidal shape which indicates that another binding mode may exist besides intercalation or/and significant cooperativity can exist between the ligand molecules …”
Section: Resultsmentioning
confidence: 70%
“…In fact, the general behavior of the persistence length A shown in Fig. 1 was previously verified by our group for the intercalators ethidium bromide (EtBr), daunomycin, psoralen and diaminobenzidine under nearly similar experimental conditions [26], [24], [27], [23], by using optical Fig. 1 Persistence length A as a function of ligand total concentration in the sample C T .…”
Section: Stretching Experimentssupporting
confidence: 65%
“…Recently our group has studied in detail the changes in the persistence and contour lengths of DNA complexes formed with various intercalating molecules [75][76][77]94,133 , by using optical tweezers in a very low force regime (F < 2 pN). We reported an abrupt structural transition in the persistence length due to drug intercalation, which is probably related to a partial denaturation of the DNA molecule due to the pulling force used to stretch the complexes 76,77,133,147 . The contour length, otherwise, does not present such a transition, increasing monotonically with drug concentration until saturation.…”
Section: B Intercalatorsmentioning
confidence: 99%
“…When there is no illumination at the sample, however, psoralen interacts with DNA by intercalative binding -see next section. The effects of covalent binding on the mechanical properties of the DNA-psoralen complexes were recently studied 94,133 . In particular, it was shown that the contour and persistence lengths of the complexes depend on the psoralen concentration and on the exposure time to UVA light 133 .…”
Section: A Covalent Ligandsmentioning
confidence: 99%